Defining Customer Export Limits in PV-Rich Low Voltage Networks - Ricciardi, Tiago R.; Petrou, Kyriacos; Franco, John; Ochoa, Luis F. (My University, 2018)
The growing adoption of residential photovoltaic (PV) systems around the world is presenting Distribution Network Operators (DNOs) with technical challenges, particularly on Low Voltage (LV) networks. The need to mitigate these issues with simple yet effective measures in countries with high PV penetrations is likely to drive the adoption of limits on the very exports that affect this infrastructure. Defining the most adequate limit, however, requires understanding the trade-offs between the technical benefits and the effects on PV owners. This work proposes two methodologies: an Optimal Power Flow (OPF)-based technique to define the export limit that solves technical problems with minimal curtailment, and a Monte Carlo-based analysis to investigate the spectrum of such trade-offs considering different PV penetrations and export limits. A real UK residential LV network with 180 customers is analyzed using realistic 1-min resolution daily load and PV generation profiles across seasons. Results demonstrate that, for DNOs, the OPF-based approach is effective in determining the most technically-adequate export limit. However, for policy makers, the spectrum of trade-offs provided by the Monte Carlo approach can help defining export limits that reduce curtailment at the expense of partially mitigating technical issues.
Keywords: Low voltage networks; optimal power flow; photovoltaics; PV management